Positive electrode single crystal material with good cycle performance, preparation method of positive electrode single crystal material and battery

Through the use of coating technology in ternary positive materials, the positive single -crystal material with single crystal appearance is prepared, the problem of insufficient circulation stability of the existing materials, and realizing efficient circulating performance and safety performance.

CN119340351APending Publication Date: 2025-01-21XIAMEN SUNYEAR ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310894563.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing ternary positive electrode materials have shortcomings in circulation stability, mainly due to side reactions between the positive electrode materials and the electrolyte, resulting in defects in the surface structure of the material.

Method used

A cathode single crystal material including a main crystalline phase material and a coating material is used. The chemical formula of the main crystalline phase material is LixNi1-y-zCoy(Mn,Zr)zO2. It is prepared through wet ball milling and calcination processes, and then the material is Coated to improve cycle performance.

Benefits of technology

The good circulation performance, diffusion coefficient, and ionic conductivity of the positive electrode materials are realized. The discharge ratio is ≥190mAh/g. The capacity retention rate of the capacity of 100 % after the cycle of 100 circles is 98.0 %. At the same time, the safety performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004349224870000111
    Figure BDA0004349224870000111
  • Figure BDA0004349224870000121
    Figure BDA0004349224870000121
Patent Text Reader

Abstract

The invention provides a positive single crystal material with good cycle performance, a preparation method thereof and a battery, the material comprises a main crystal phase material and a coating material, the chemical formula of the main crystal phase material is LixNi1-y-zCoy (Mn, Zr) zO2, x is greater than or equal to 1.02 and less than or equal to 1.10, y is greater than or equal to 0.05 and less than or equal to 0.20, z is greater than or equal to 0.20 and less than or equal to 0.40, Mn / Zr is greater than or equal to 20 and less than or equal to 100, and the coating material is selected from one or more of Al2O3, TiO2, BaTiO3, Li7La3ZrTiO12, CeO2 and SiO2. The solid nickel salt, the solid cobalt salt, the solid manganese salt and the lithium compound are subjected to wet ball milling according to a specific proportion, calcination is performed after spray drying or filter pressing drying, and then the obtained LixNi1-y-zCoy (Mn, Zr) zO2 with the single crystal particle morphology is coated, so that the situation that due to the fact that the LixNi1-y-zCoy (Mn, Zr) zO2 material makes direct contact with an electrolyte, a crystal structure is damaged, lattice distortion is caused, and the service life of the material is prolonged is avoided. And finally, the phenomenon that the capacity is greatly attenuated in the circulation process occurs. The positive electrode single crystal material obtained by the invention has a single crystal morphology, and can obtain the specific discharge capacity greater than or equal to 190mAh / g under the voltage of 3.0-4.4 V and the temperature of 0.1 C, 100 cycles of power-off, and the capacity retention ratio of 98.0%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to a positive electrode single crystal material with good cycle performance, a preparation method thereof, and a battery. Background Art

[0002] With the rapid development of electric vehicles (EV) and hybrid electric vehicles (HEV), higher requirements are placed on longer battery life. Ternary cathode materials have attracted the attention of many battery companies due to their high specific capacity and high energy density. Especially after the successful promotion of Tesla cars (using ternary material batteries), ternary material batteries have been put on the stage.

[0003] Although the existing commercial ternary materials have a high energy density and can meet people's daily travel needs, their cycle stability still needs to be further improved. At present, the main reason for the poor cycle performance is the side reaction between the positive electrode material and the electrolyte, which causes structural defects on the surface of the material. Summary of the invention

[0004] The object of the present invention is to provide a positive electrode single crystal material with good cycle performance. The material is in the form of single crystal particles and has good cycle performance, diffusion coefficient and ion conductivity.

[0005] Another object of the present invention is to provide a method for preparing a positive electrode single crystal material with good cycle performance. The method is simple to operate and is green and environmentally friendly, and is suitable for industrial large-scale production.

[0006] The third object of the present invention is to provide a method for preparing a battery, which is simple to operate and has controllable parameters and is suitable for stable production.

[0007] A fourth object of the present invention is to provide a battery having good cycle performance and high safety performance.

[0008] The present invention solves the technical problem by adopting the following technical solutions.

[0009] The present invention provides a positive electrode single crystal material with good cycle performance, including a main crystal phase material and a coating material, wherein the chemical formula of the main crystal phase material is: Li x Ni 1-y-z Co y (Mn , Zr) z O2, wherein 1.02≤x≤1.10, 0.05≤y≤0.20, 0.20≤z≤0.40, 20≤Mn / Zr≤100, and the coating material is selected from Al2O3, TiO2, BaTiO3, Li7La3ZrTiO 12, CeO2, SiO2 or more.

[0010] The present invention provides a method for preparing a positive electrode single crystal material with good cycle performance, comprising the following steps:

[0011] S1, wet-milling nickel salt, cobalt salt, lithium salt, manganese salt and ZrO2, and calcining to obtain the main crystalline phase material;

[0012] S2. The main crystalline phase material and the coating material are mixed and calcined to obtain the positive electrode single crystal material with good cycle performance.

[0013] The present invention provides a method for preparing a battery, comprising the following steps:

[0014] Adding an additive to the positive electrode single crystal material with good cycle performance and then ball milling to obtain a slurry; then coating the slurry to obtain a membrane; finally, drying and compacting the membrane and combining it with a lithium sheet to obtain a battery.

[0015] The present invention also provides a battery, which is manufactured according to the manufacturing method of the battery.

[0016] The positive electrode single crystal material with good cycle performance and the preparation method thereof, and the battery of the embodiment of the present invention have the following beneficial effects:

[0017] The present invention wet-mills solid nickel salt, solid cobalt salt, solid manganese salt and lithium compound according to a specific ratio to a particle size D50=0.15-1.0 μm, spray-drying or filter-press drying to obtain a solid mixture, and calcining the mixture at 850-1050° C. for 3-7 hours, and then calcining the obtained single crystal particle morphology of Li x Ni 1-y-z Co y (Mn , Zr) z O2 is coated to avoid the x Ni 1-y-z Co y (Mn , Zr) z The direct contact between the O2 material and the electrolyte causes the crystal structure to be destroyed, resulting in lattice distortion and ultimately a significant decrease in capacity during the cycle.

[0018] Compared with the traditional method of first preparing a precursor and then lithiation, and then doping and coating to obtain the positive electrode single crystal material, the preparation method of the positive electrode single crystal material of the present invention has a simple process and can avoid the defects of emitting a large amount of acid and alkali substances and poor control of solution concentration during the precursor production process. It not only effectively solves the environmental protection problem, but also the obtained positive electrode single crystal material has a single crystal morphology. At a voltage of 3.0 to 4.4V and 0.1C, a discharge specific capacity of ≥190mAh / g can be obtained, and the capacity retention rate is 98.0% after 100 cycles of deducting power. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0020] The following is a detailed description of the positive electrode single crystal material and its preparation method and the battery with good cycle performance in the embodiments of the present invention.

[0021] The embodiment of the present invention provides a positive electrode single crystal material with good cycle performance, including a main crystal phase material and a coating material, wherein the chemical formula of the main crystal phase material is: Li x Ni 1-y-z Co y (Mn , Zr) z O2, wherein 1.02≤x≤1.10, 0.05≤y≤0.20, 0.20≤z≤0.40, 20≤Mn / Zr≤100, and the coating material is selected from Al2O3, TiO2, BaTiO3, Li7La3ZrTiO 12 , CeO2, SiO2 or more.

[0022] Furthermore, in a preferred embodiment of the present invention, in the positive electrode single crystal material with good cycle performance, the mass fraction of the main crystalline phase material is 99.0-99.5%, and the mass fraction of the coating material is 0.5-1.0%.

[0023] Furthermore, in a preferred embodiment of the present invention, the particle morphology of the positive electrode single crystal material with good cycle performance is a single crystal morphology. The positive electrode single crystal material of the present invention has a single crystal morphology structure, good dispersion and uniformity, and excellent performance.

[0024] The present invention also provides a method for preparing a positive electrode single crystal material with good cycle performance, comprising the following steps:

[0025] S1. Wet-mill nickel salt, cobalt salt, lithium salt, manganese salt and ZrO2, and calcine to obtain the main crystalline phase material.

[0026] Furthermore, in a preferred embodiment of the present invention, the calcination is carried out at 850-1050° C. for 3-7 hours in air or oxygen atmosphere.

[0027] S2. Mix the main crystalline phase material and the coating material, and after calcination, obtain the positive electrode single crystal material with good cycle performance. Coating the material has two main functions: one is to add a protective layer on the surface of the material, reduce the side reaction between the material and the electrolyte, inhibit the dissolution of transition metal ions, and reduce the collapse of the material structure during repeated charge and discharge, thereby optimizing the cycle performance of the material; the other is to improve the diffusion coefficient and ion conductivity of lithium ions and reduce the diffusion impedance of lithium ions to a certain extent through coating.

[0028] The present invention can effectively reduce the side reaction between the electrolyte and the active material by coating the surface of the main crystalline phase material, thereby playing the role of a protective layer, and at the same time is conducive to the optimization of the surface structure of the layered oxide positive electrode material, effectively improving the material's cycle stability and thermal stability, etc. In addition, the present invention adopts a wet method to make a single crystal positive electrode material, which not only avoids the precursor process, but also the obtained particle morphology is a single crystal particle morphology, and then through appropriate coating, the side reaction between the material surface and the electrolyte is further reduced, and at a voltage of 4.4V, good cycle performance can be obtained, and the material safety performance is improved.

[0029] Furthermore, in a preferred embodiment of the present invention, the calcination temperature is 450-750°C, and the calcination time is 3-7h. Preferably, the calcination temperature is 500-650°C, and the calcination time is 4-6h, and more preferably, the calcination temperature is 560-630°C, and the calcination time is 5h. Calcination and coating at a shorter holding time can ensure that the coating material is on the surface and does not dissolve into the main crystal phase.

[0030] The present invention wet-mills solid nickel salt, solid cobalt salt, solid manganese salt and lithium compound according to a specific ratio to a particle size D50=0.15-1.0 μm, spray-drying or filter-press drying to obtain a solid mixture, and calcining the mixture at 850-1050° C. for 3-7 hours, and then calcining the obtained single crystal particle morphology of Li x Ni 1-y-z Co y (Mn , Zr) z O2 is coated to avoid the x Ni 1-y-z Co y (Mn , Zr)z The direct contact between the O2 material and the electrolyte causes the crystal structure to be destroyed, resulting in lattice distortion and ultimately a significant decrease in capacity during the cycle.

[0031] Compared with the traditional method of first preparing a precursor and then lithiation, and then doping and coating to obtain the positive electrode single crystal material, the preparation method of the positive electrode single crystal material of the present invention has a simple process and can avoid the defects of emitting a large amount of acid and alkali substances and poor control of solution concentration during the precursor production process. It not only effectively solves the environmental protection problem, but also the obtained positive electrode single crystal material has a single crystal morphology. At a voltage of 3.0 to 4.4V and 0.1C, a discharge specific capacity of ≥190mAh / g can be obtained, and the capacity retention rate is 98.0% after 100 cycles of deducting power.

[0032] The present invention also provides a method for preparing a battery, comprising the following steps:

[0033] Adding an additive to the positive electrode single crystal material with good cycle performance and then ball milling to obtain a slurry; then coating the slurry to obtain a membrane; finally, drying and compacting the membrane and combining it with a lithium sheet to obtain a battery.

[0034] Furthermore, in a preferred embodiment of the present invention, the auxiliary agent includes a conductive agent, a binder and a solvent, and the mass ratio of the positive electrode single crystal material with good cycle performance, the conductive agent and the binder is 8:1:1. Preferably, the conductive agent is carbon black or graphite, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

[0035] Furthermore, in a preferred embodiment of the present invention, the drying step is: keeping the film at 50°C to 65°C for 3 hours, and then keeping the film at 110°C and -0.1MPa vacuum for 12 hours to remove organic matter in the film, wherein the heating rate is less than 50°C / h. The compaction condition of the present invention is: rolling the film in a roller machine with a gap of 75 to 85 μm to obtain a film with a certain density.

[0036] Furthermore, in a preferred embodiment of the present invention, the membrane and the Li sheet are assembled in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm, which can effectively eliminate the negative effects of material oxidation and moisture absorption.

[0037] The present invention also provides a battery, which is prepared according to the battery preparation method. The battery prepared by the present invention has a discharge specific capacity of ≥190mAh / g at a voltage of 3.0-4.4V and 0.1C, and a capacity retention rate of 98.0% after 100 cycles of deducting power.

[0038] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0039] Example 1

[0040] This embodiment provides a battery, which is prepared according to the following method:

[0041] (1) According to the ratio of each component in No. 1 shown in Table 1, nickel salt, cobalt salt, lithium salt, manganese salt and ZrO2 are weighed respectively, and wet ball milled to a particle size D50 less than 2.0 μm, and then calcined at 990° C. for 6 h, and then crushed to obtain the main crystalline phase material.

[0042] (2) The main crystal phase material and the coating material are mixed according to the ratio of the main crystal phase material and the coating material in No. 1 shown in Table 1, and then calcined at 570°C for 6h to obtain a positive electrode single crystal material (Li 1.06 Ni 0.50 Co 0.15 Mn 0.345 Zr 0.005 O2).

[0043] (3) Add appropriate amounts of carbon black, PVDF and N-methylpyrrolidone to the positive electrode single crystal material with good cycle performance obtained in step (2), wherein the mass ratio of the positive electrode single crystal material with good cycle performance, carbon black and PVDF is 8:1:1. Then, the slurry is ball-milled in a ball mill for 2 hours using zirconium oxide balls as ball-milling media to obtain a slurry. Finally, the slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying conditions are: keep warm for 3 hours under atmospheric conditions of 50°C, then remove organic matter in the membrane at 110°C and -0.1MPa vacuum, and keep warm for 12 hours. The heating rate of the entire removal process is required to be less than 50°C / h.

[0044] (4) The film obtained in step (3) is rolled in a double-roll mill at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.

[0045] (5) Assemble the membrane and lithium sheet obtained in step (4) in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a button cell sample.

[0046] Example 2

[0047] This embodiment provides a battery, which is prepared according to the following method:

[0048] (1) According to the ratio of each component in No. 2 shown in Table 1, nickel salt, cobalt salt, lithium salt, manganese salt and ZrO2 are weighed respectively, and wet ball milled to a particle size D50 less than 2.0 μm, and then calcined at 935° C. for 7 h, and then crushed to obtain the main crystalline phase material.

[0049] (2) The main crystal phase material and the coating material are mixed according to the ratio of the main crystal phase material and the coating material in No. 2 shown in Table 1, and then calcined at 595°C for 5.5h to obtain a positive electrode single crystal material (Li 1.09 Ni 0.6 0Co 0.20 Mn 0.193 Zr 0.007 O2).

[0050] (3) Add appropriate amounts of carbon black, PVDF and N-methylpyrrolidone to the positive electrode single crystal material with good cycle performance obtained in step (2), wherein the mass ratio of the positive electrode single crystal material with good cycle performance, carbon black and PVDF is 8:1:1. Then, the slurry is ball-milled in a ball mill for 2 hours using zirconium oxide balls as ball-milling media to obtain a slurry. Finally, the slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying conditions are: keep warm for 3 hours under atmospheric conditions of 50°C, then remove organic matter in the membrane at 110°C and -0.1MPa vacuum, and keep warm for 12 hours. The heating rate of the entire removal process is required to be less than 50°C / h.

[0051] (4) The film obtained in step (3) is rolled in a double-roll mill at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.

[0052] (5) Assemble the membrane and lithium sheet obtained in step (4) in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a button cell sample.

[0053] Example 3

[0054] This embodiment provides a battery, which is prepared according to the following method:

[0055] (1) According to the ratio of each component in No. 3 shown in Table 1, nickel salt, cobalt salt, lithium salt, manganese salt and ZrO2 are weighed respectively, and wet ball milled to a particle size D50 less than 2.0 μm, and then calcined at 915° C. for 6.5 h, and then crushed to obtain the main crystalline phase material.

[0056] (2) The main crystal phase material and the coating material are mixed according to the ratio of the main crystal phase material and the coating material in No. 3 shown in Table 1, and then calcined at 600°C for 4.5h to obtain a positive electrode single crystal material (Li 1.04 Ni 0.6 5Co 0.13 Mn 0.211 Zr 0.009 O2).

[0057] (3) Add appropriate amounts of carbon black, PVDF and N-methylpyrrolidone to the positive electrode single crystal material with good cycle performance obtained in step (2), wherein the mass ratio of the positive electrode single crystal material with good cycle performance, carbon black and PVDF is 8:1:1. Then, the slurry is ball-milled in a ball mill for 2 hours using zirconium oxide balls as ball-milling media to obtain a slurry. Finally, the slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying conditions are: keep warm for 3 hours under atmospheric conditions of 50°C, then remove organic matter in the membrane at 110°C and -0.1MPa vacuum, and keep warm for 12 hours. The heating rate of the entire removal process is required to be less than 50°C / h.

[0058] (4) The film obtained in step (3) is rolled in a double-roll mill at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.

[0059] (5) Assemble the membrane and lithium sheet obtained in step (4) in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a button cell sample.

[0060] Example 4

[0061] This embodiment provides a battery, which is prepared according to the following method:

[0062] (1) According to the ratio of each component in No. 4 shown in Table 1, nickel salt, cobalt salt, lithium salt, manganese salt and ZrO2 are weighed respectively, and wet ball milled to a particle size D50 less than 2.0 μm, and then calcined at 985°C for 6.5 h, and then crushed to obtain the main crystalline phase material.

[0063] (2) The main crystal phase material and the coating material are mixed according to the ratio of the main crystal phase material and the coating material in No. 4 shown in Table 1, and then calcined at 700°C for 5.0h to obtain a positive electrode single crystal material (Li 1.06 Ni 0.5 5Co 0.15 Mn 0.292 Zr 0.008 O2).

[0064] (3) Add appropriate amounts of carbon black, PVDF and N-methylpyrrolidone to the positive electrode single crystal material with good cycle performance obtained in step (2), wherein the mass ratio of the positive electrode single crystal material with good cycle performance, carbon black and PVDF is 8:1:1. Then, the slurry is ball-milled in a ball mill for 2 hours using zirconium oxide balls as ball-milling media to obtain a slurry. Finally, the slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying conditions are: keep warm for 3 hours under atmospheric conditions of 50°C, then remove organic matter in the membrane at 110°C and -0.1MPa vacuum, and keep warm for 12 hours. The heating rate of the entire removal process is required to be less than 50°C / h.

[0065] (4) The film obtained in step (3) is rolled in a double-roll mill at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.

[0066] (5) Assemble the membrane and lithium sheet obtained in step (4) in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a button cell sample.

[0067] Example 5

[0068] This embodiment provides a battery, which is prepared according to the following method:

[0069] (1) According to the ratio of each component in No. 5 shown in Table 1, nickel salt, cobalt salt, lithium salt, manganese salt and ZrO2 are weighed respectively, and wet ball milled to a particle size D50 less than 2.0 μm, and then calcined at 1020° C. for 3.5 h, and then crushed to obtain the main crystalline phase material.

[0070] (2) The main crystal phase material and the coating material are mixed according to the ratio of the main crystal phase material and the coating material in No. 5 shown in Table 1, and then calcined at 500°C for 4.5h to obtain a positive electrode single crystal material (Li 1.08 Ni 0.5 0Co 0.20 Mn 0.294 Zr 0.006 O2).

[0071] (3) Add appropriate amounts of carbon black, PVDF and N-methylpyrrolidone to the positive electrode single crystal material with good cycle performance obtained in step (2), wherein the mass ratio of the positive electrode single crystal material with good cycle performance, carbon black and PVDF is 8:1:1. Then, the slurry is ball-milled in a ball mill for 2 hours using zirconium oxide balls as ball-milling media to obtain a slurry. Finally, the slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying conditions are: keep warm for 3 hours under atmospheric conditions of 50°C, then remove organic matter in the membrane at 110°C and -0.1MPa vacuum, and keep warm for 12 hours. The heating rate of the entire removal process is required to be less than 50°C / h.

[0072] (4) The film obtained in step (3) is rolled in a double-roll mill at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.

[0073] (5) Assemble the membrane and lithium sheet obtained in step (4) in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a button cell sample.

[0074] Example 6

[0075] This embodiment provides a battery, which is prepared according to the following method:

[0076] (1) According to the ratio of each component in No. 6 shown in Table 1, nickel salt, cobalt salt, lithium salt, manganese salt and ZrO2 are weighed respectively, and wet ball milled to a particle size D50 less than 2.0 μm, and then calcined at 920° C. for 4.0 h, and then crushed to obtain the main crystalline phase material.

[0077] (2) The main crystal phase material and the coating material are mixed according to the ratio of the main crystal phase material and the coating material in No. 6 shown in Table 1, and then calcined at 520° C. for 5.0 h to obtain a positive electrode single crystal material (Li 1.08 Ni 0.6 3Co 0.10 Mn 0.262 Zr 0.008 O2).

[0078] (3) Add appropriate amounts of carbon black, PVDF and N-methylpyrrolidone to the positive electrode single crystal material with good cycle performance obtained in step (2), wherein the mass ratio of the positive electrode single crystal material with good cycle performance, carbon black and PVDF is 8:1:1. Then, the slurry is ball-milled in a ball mill for 2 hours using zirconium oxide balls as ball-milling media to obtain a slurry. Finally, the slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying conditions are: keep warm for 3 hours under atmospheric conditions of 50°C, then remove organic matter in the membrane at 110°C and -0.1MPa vacuum, and keep warm for 12 hours. The heating rate of the entire removal process is required to be less than 50°C / h.

[0079] (4) The film obtained in step (3) is rolled in a double-roll mill at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.

[0080] (5) Assemble the membrane and lithium sheet obtained in step (4) in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a button cell sample.

[0081] Table 1 Material ratio table

[0082]

[0083] Test Example 1

[0084] In this test example, the battery samples obtained in Examples 1 to 6 were tested at a voltage of 3.0 to 4.4 V and a condition of 0.1 C. The test results are shown in Table 2.

[0085] Table 2 Performance test results

[0086]

[0087] As can be seen from Table 2, the battery prepared by the positive electrode single crystal material obtained by the above method has a discharge capacity of at least 190.29 mAh / g and a maximum of 196.07 mAh / g at a voltage of 3.0 to 4.4 V, and a capacity retention rate of greater than or equal to 98% after 100 cycles. The material has good cycle performance and high safety performance.

[0088] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A positive electrode single crystal material with good cycle performance, characterized in that: It includes a main crystal phase material and a coating material, wherein the chemical formula of the main crystal phase material is: Li x Ni 1-y-z Co y (Mn , Zr) z O2, wherein 1.02≤x≤1.10, 0.05≤y≤0.20, 0.20≤z≤0.40, 20≤Mn / Zr≤100, and the coating material is selected from Al2O3, TiO2, BaTiO3, Li7La3ZrTiO 12 , CeO2, SiO2 or more.

2. The positive electrode single crystal material with good cycle performance according to claim 1, characterized in that: In the positive electrode single crystal material with good cycle performance, the mass fraction of the main crystal phase material is 99.0-99.5%, and the mass fraction of the coating material is 0.5-1.0%.

3. The positive electrode single crystal material with good cycle performance according to claim 1, characterized in that: The particle morphology of the positive electrode single crystal material with good cycle performance is a single crystal morphology.

4. A method for preparing a positive electrode single crystal material with good cycle performance, characterized in that: The following steps are involved: S1, wet-milling nickel salt, cobalt salt, lithium salt, manganese salt and ZrO2, and calcining to obtain the main crystalline phase material; S2. The main crystalline phase material and the coating material are mixed and calcined to obtain the positive electrode single crystal material with good cycle performance.

5. The preparation method according to claim 4, characterized in that: In step S1, the calcination step is: calcining at 850-1050° C. for 3-7 hours in air or oxygen atmosphere.

6. The preparation method according to claim 4, characterized in that: In step S2, the calcination temperature is 450-750°C, and the calcination time is 3-7h.

7. A method for preparing a battery, characterized in that: The following steps are involved: Adding an additive to the positive electrode single crystal material with good cycle performance and then ball milling to obtain a slurry; then coating the slurry to obtain a membrane; finally, drying and compacting the membrane and combining it with a lithium sheet to obtain a battery.

8. The preparation method according to claim 7, characterized in that: The auxiliary agent includes a conductive agent, a binder and a solvent, and the mass ratio of the positive electrode single crystal material with good cycle performance, the conductive agent and the binder is 8:1:

1.

9. The preparation method according to claim 7, characterized in that: The drying step is: keeping warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keeping warm for 12 hours under 110°C and -0.1MPa vacuum, wherein the heating rate is less than 50°C / h.

10. A battery, characterized in that: Prepared according to the preparation method according to any one of claims 7 to 9.